Refractive outcomes after intravitreal injection of antivascular endothelial growth factor versus laser photocoagulation for retinopathy of prematurity: a meta-analysis - Kong, Qihang; Ming, Wai-kit; Mi, Xue-Song (BMJ open, 2021)
ObjectiveTo determine the effects of the intraocular injection of antivascular endothelial growth factor (anti-VEGF) drugs on the refractive status of infants with retinopathy of prematurity (ROP).DesignSystematic review and meta-analysis of the refractive status of infants with ROP who receive anti-VEGF drugs.Data sourcesThe PubMed, Web of Science and Embase databases and the ClinicalTrials.gov website were searched up to June 2020.Eligibility criteria when selecting studiesWe included randomised controlled trials (RCTs) and observational studies that compared refractive errors between anti-VEGF drug and laser therapies.Data extraction and synthesisData extraction and risk-of-bias assessments were conducted by two independent reviewers. We used a random-effect model to pool outcomes. The outcome measures were the spherical equivalents, axial length (AL), anterior chamber depth (ACD) and lens thickness (LT).ResultsThirteen studies involving 1850 eyes were assessed: 914 in the anti-VEGF drug group, and 936 in the control (laser) group. Children who received anti-VEGF drug treatment had less myopia than those who received laser therapy (mean difference=1.80 D, 95% CI 0.97 to 2.63, p＜0.0001, I2=78%). The AL, ACD and LT did not reach statistical significance difference between the two groups. The current evidence indicates that the refractive safety in children with ROP is better for anti-VEGF drug treatment than for laser therapy.ConclusionsThis meta-analysis indicates that anti-VEGF drug therapy results in less myopia compared with laser therapy. However, there are relatively few published articles on refractive errors in ROP, and so high-quality and powerful RCTs are needed in the future.PROSPERO registration numberCRD42020160673.